The Implementation of 2013 Curriculum Learning Models based on English Teachers’ Experience at SMP Negeri 4 Gorontalo - Hanafi Sumardin Yabie; Nurlaila Husain; Helena Badu (Ideas Publishing, 2021)
This is a qualitative descriptive research which aims to know what learning models are being implemented in English learning process at SMP Negeri 4 Gorontalo based on 2013 curriculum. The data collection technique employs interview, in which the participant is the four English teachers at SMP Negeri 4 Gorontalo. The data analysis technique uses the interactive analysis steps from Miles & Huberman, they are data collection, data reduction, data display, and conclusion drawing. The finding shows that there are three learning models implemented in the English learning process, including project-based learning, scientific approach with ICT-based media, and conventional learning model. All those learning model implemented have their own syntaxes and specified objective. Thus, based on the finding, it can be concluded that learning model that is actually implemented more often by the English teachers to strengthen the scientific process based on the Permendikbud Number 22 of 2016 is project-based learning. Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk mengetahui model pembelajaran apa saja yang diterapkan dalam proses pembelajaran bahasa Inggris di SMP Negeri 4 Gorontalo berdasarkan kurikulum 2013. Teknik pengumpulan data menggunakan wawancara, dimana partisipan adalah empat guru bahasa Inggris di SMP Negeri 4 Gorontalo. Teknik analisis data menggunakan langkah-langkah analisis interaktif dari Miles & Huberman yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa terdapat tiga model pembelajaran yang diterapkan dalam proses pembelajaran bahasa Inggris, yaitu project-based learning, pendekatan saintifik dengan media berbasis TIK, dan model pembelajaran konvensional. Semua model pembelajaran yang diterapkan memiliki sintaks dan tujuan masing-masing. Dengan demikian, berdasarkan temuan dapat disimpulkan bahwa model pembelajaran yang sering diterapkan oleh guru bahasa Inggris untuk memperkuat proses saintifik berdasarkan Permendikbud Nomor 22 Tahun 2016 adalah project-based learning.